Analyzing Chinese parents' and teachers' perception of play, children's emotional needs and therapy: implications for seeking help - Cao, Huiting (Frontiers in Psychology, 2023)
Before going through play therapy with children, parents' consent is usually needed. Thus, Parents' perception of play therapy can be a very important variable that influences the extent to which children are exposed to play therapy. Previous research has demonstrated the significant influence of social-cultural factors on people's perceptions of play therapy. This may in turn influence parents' decision about whether their children will participate in play therapy. This study explores the factors that influence Chinese parents' decisions on their children's engagement in play therapy from a social-cultural perspective. Methods: This small-scale research includes the following: a questionnaire with 16 parents; three one-to-one semi-structured interviews with three parents; and one focus group with 3 teachers.The results showed that Chinese parents' perceptions of therapy are mostly negative, which may reduce the desire of parents to let their children become involved with play therapy. The children's academic stress and the parents' economic pressures indicate a barrier for families to commit time and money to play therapy. Parents' confidence in their ability to recognize children's emotions, their lack of knowledge about play therapy, and the process of obtaining help from mental health services for children could be another barriers preventing engagement with play therapy. Discussions: Even though the research is conducted with a very limited sample size and the results cannot represent the wider population, this research provides some insights into this issue that can be explored in detail in future research, to re-evaluate the results and form a more concrete theory within a wider population in China.Play can be meaningful to children in many ways. Shrinivasa et al.(1) suggested that play "is the method most children use to explore the world and to comprehend relationships, and it also helps them to understand the past and also to prepare for the future" (p.82). In relation to this function of play for children, Howard (2) further emphasized the importance of understanding the benefits of play, arguing children use play to connect to many aspects of their